2008
DOI: 10.1515/bot.2008.023
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproductive phenology of Pterocladiella capillacea (Rhodophyta: Gelidiales) from the southern Adriatic Sea

Abstract: Growth, external morphology and reproductive phenology of a southern Adriatic population of Pterocladiella capillacea from a marine cave were investigated. Production of new uprights from creeping axes was limited to late autumn-winter; upright growth in length and branching order increase reached their maxima in late summer. Tetrasporic fronds were dominant from June to September, with a peak in July, while cystocarpic uprights were rather rare and recorded in August only. Two stable, distinct morphotypes occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Red algae of the genus Pterocladia are used for industrial production of gelling galactans and are commonly distributed in the seas of Lebanon, Egypt, Brazil, Italy and other countries (Wassef et al, 2002;Silva et al, 2010;Bottalico et al, 2008). Previous researches have discussed the composition and the properties of polysaccharides from the red algae Pterocladia capillacea.…”
Section: Introductionmentioning
confidence: 99%
“…Red algae of the genus Pterocladia are used for industrial production of gelling galactans and are commonly distributed in the seas of Lebanon, Egypt, Brazil, Italy and other countries (Wassef et al, 2002;Silva et al, 2010;Bottalico et al, 2008). Previous researches have discussed the composition and the properties of polysaccharides from the red algae Pterocladia capillacea.…”
Section: Introductionmentioning
confidence: 99%
“…A different degree of deviation from the balanced haploid:diploid ratio is often observed and tetrasporophytes have been described as several orders of magnitude more frequent than gametophytes, the sexual phases being completely absent in some cases (Akatsuka, 1986;Santelices, 1988;Santos & Duarte, 1996;Bottalico & al., 2008). The unequal distribution of tetrasporophytes and gametophytes was explained by physiological differences between the two phases (Santelices, 1990), although indicated that physiological characteristics were not responsible for the scarcity of gametophytes in the populations of G. canariense of Gran Canaria (Canary Islands).…”
Section: Discussionmentioning
confidence: 99%
“…Also, many researchers have studied the composition and the properties of polysaccharides from the red algae Pterocladia capillacea. Pterocladia as a red algae genus is used for industrial production of gelling galactans and is commonly distributed in the seas of Lebanon, Egypt, Brazil, Italy and other countries [16,17].…”
Section: Introductionmentioning
confidence: 99%